REPRESENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM FILM JANGAN PANGGIL MAMA KAFIR: ANALISIS TOLERANSI BERAGAMA DAN DINAMIKA DIALOG - Eni Rakhmawati; Milati Farkhatunnisa; Yesta Puja Ayu Rasmita; Amellia Putri; Nihlatul Faridah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the representation of tolerance in the film *Jangan Panggil Mama Kafir* and to examine its potential as a medium for teaching critical tolerance. The study employs a qualitative approach of a descriptive-analytical nature. The research data consists of dialogues, scenes, and narratives in the film that are relevant to the themes of tolerance, intolerance, and the dynamics of dialogue. Data collection techniques include observation, documentation, and literature review, while data analysis employs content analysis. The findings reveal that the film *Jangan Panggil Mama Kafir* portrays tolerance as a dynamic and reflective social process, inseparable from interpersonal conflict and negotiation. Additionally, the film also portrays various forms of intolerance triggered by prejudice, stereotypes, and the failure to establish open and equal dialogue. Other findings indicate a tendency toward the loss of space for dialogue in social interactions, which contributes to increased conflict. Nevertheless, the film also presents the potential for reconstructing dialogue through the reflective moments experienced by the characters. Furthermore, this study found that the film has the potential to serve as a medium for critical tolerance education because it is able to present social reality in a contextual manner and encourage viewers to think reflectively about social phenomena. Therefore, the use of films in education can serve as an effective alternative strategy for fostering an attitude of tolerance that is not only normative but also critical and contextual.